The cholinergic system and neostriatal memory functions - Havekes, Robbert (2010)
The striatum is one of the major forebrain regions that strongly express muscarinic and nicotinic cholinergic receptors. This article reviews the current knowledge and our new findings about the striatal cholinoceptive organization and its role in a variety of cognitive functions. Pharmacological and genetic manipulations have indicated that the cholinergic and dopaminergic system in the striatum modulate each other’s function. In addition to modulating the dopaminergic system, nicotinic cholinergic receptors facilitate GABA release, whereas muscarinic receptors attenuate GABA release. The striatal cholinergic system has also been implicated in various cognitive functions including procedural learning and intradimensional set shifting. Together, these data indicate that the cholinergic system in the striatum is involved in a diverse set of cognitive functions through interactions with other neurotransmitter systems including the dopaminergic and GABAergic systems.